Advances in Human Factors in Training, Education, and Learning Sciences Proceedings of the AHFE 2017 International Conference on Human Factors in Training, Education, and Learning Sciences, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Andre, Terence; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book focuses on the importance of human factors in optimizing the learning and training process. It reports on the latest research and best practices and discusses key principles of behavioral and cognitive science, which are extremely relevant to the design of instructional content and new technologies to support mobile and multimedia learning, virtual training and web-based learning, among others, as well as performance measurements, social and adaptive learning and many other types of educational technologies, with a special emphasis on those important in the corporate, higher education, and military training contexts. Based on the AHFE 2017 Conference on Human Factors in Training, Education, and Learning Sciences, held July 17-21, 2017 in Los Angeles, California, the book offers a timely perspective on the role of human factors in education. It highlights important new ideas and will foster new discussions on how to optimally design learning experiences.
Keywords: Computational intelligence; User interfaces (Computer systems).; Human-computer interaction; Educational technology; Cognitive psychology; Computational Intelligence; User Interfaces and Human Computer Interaction; Digital Education and Educational Technology; Cognitive Psychology